A Mixed-Methods Study to Explore Stage of Readiness and Intention of Micro and Small Enterprises to Adopt Mobile Money in Indonesia - Suhud, Usep; Hidayat, Nurdin (International Journal of Business, Economics and Management, 2015)
The objectives of this study are to understand the stage of readiness of micro and small entrepreneurs to adopt mobile money service, and to explore factors that influence mobile money acceptance in an Indonesia setting. Micro and small enterprises were expected to modify people behaviour, from cash oriented to digital. The authors implemented a mixed-methods study with the qualitative approach was in the first step. The qualitative data were collected in an industrial cluster of traditional batik textile in West Java Province, Indonesia. This first stage of study focussed on current financial transaction methods, attitude on mobile money, and intention to adopt mobile money. Thirty-one entrepreneurs participated in face-to-face interviews. Findings of the qualitative study were illustrated into the proposed model to be examined in the quantitative study. Indicators for the instrument were also taken and adapted from those findings. Furthermore, the quantitative study was conducted in Jakarta, attracting 181 micro and small entrepreneurs with various backgrounds of industries. The quantitative data were analysed using exploratory and confirmatory factor analyses. Four of eleven hypotheses were accepted. This study carried out findings that to predict intention in adopting mobile money, micro and small entrepreneurs were influenced by attitude and social influence whereas attitude was influenced by perceived credibility and perceived and usefulness.